The Functional outcome following anterior cervical discectomy and fusion for single level cervical degenerative disc disease: a prospective single institutional study - Lamichhane, Somraj; Panta, Sujata; Acharya, Devendra (Nepal Journal of Neuroscience, 2020)
Introduction: Cervical degenerative disc diseases leading to cervical spondylotic myelopathy (CSM) is one the most common cause of disability in elderly population that progresses with age with continuation of degree of degeneration. Objective: To assess the functional outcome following ACDF in single-level cervical degenerative disc disease in terms of improvement in the mJOA scoring system and postoperative complications. Materials and methods: Eighteen patients with single level cervical degenerative disc diseases who presented at the college of medical sciences from May 2018 to October 2019 fulfilling the inclusion criteria (single-level cervical degenerative disc disease with age between 40 to 70 years with progressive neurological deficits, features of cervical spondylotic myelopathy and patients with mild grade who failed four weeks of conservative treatment and progressed to moderate or severe grades) were included in the study. All patients underwent Anterior Cervical Discectomy and Fusion (ACDF); with tricortical iliac crest graft with cervical plate and screws in 13 patients and polyether ether ketone (PEEK) cage placement in five patients. Patients were assessed using mJOA scoring system and graded into mild, moderate and severe myelopathy. Post-operatively patients were assessed for improvement in terms of mJOA scores at four weeks and three months follow-up. They were also assessed for development of any post-operative complications and documented accordingly. Statistical analysis was done using the Statistical Package for the Social Sciences version 20 software. Results: Out of 18 patients, at the time of presentation 12 were in moderate grade and six were in severe grade. During subsequent follow up at four weeks and three months, patients showed progressive improvement. 15 patients improved to mild grade while two remained in moderate grade and one in severe grade during three months postoperative assessment. One patient each developed dysphagia, hoarseness and superficial wound infection that were managed conservatively. Conclusion: Anterior cervical discectomy and fusion is one of the effective and safe treatments for single-level degenerative cervical disc disease associated with cervical spondylotic myelopathy with minimal complications.